Using Promotional Strategies to Increase the Use of Miswak among Teenagers in Saudi Arabia (European Journal of Behavioral Sciences, 2023)
Miswak is a chewing stick that has been used in Muslim communities across the world for over 1,500 years as an oral hygiene aid. There is evidence to support its clinical effectiveness in plaque management when used alone or in conjunction with a conventional toothbrush. However, evidence of its deleterious effects on periodontal health is equivocal. To study culturally acceptable strategies for promoting oral health practices and preventing illness among adolescents in Saudi Arabia, advertisements were assessed for their ability to engage and open up new communication channels for oral health messages. The aim is to encourage adolescents to adopt the habit of using miswak to improve their oral hygiene, wherever they may be. The data for this study was collected from 116 teenage respondents from Saudi Arabia. The mean age of the study participants was 16.66 ± 0.943 years, with a median age of 17 and a range from 12 to 17. The study included 66 males (56.9%) and 50 females (43.1%). Furthermore, the overall mean assessments of both advertisements were negative due to several problems with the design and use of pictures in the ads. The analysis of this study show that a more standardised method of advertisement is required to properly gain the attention of this generation of adolescents in Saudi Arabia. In addition, the individuals who took part in the research believed that social media is the most suitable venue for conveying messages promoting miswak. To be able to communicate effectively about oral health messaging, one must first have a solid understanding of the advertising messages that are relevant to oral health, as well as the influence of religion. Another prerequisite for the creation of effective advertising is knowledge of media platforms and the impacts that these platforms have on the behaviour of teenagers. Successful communication could make youths in Saudi Arabia likelier to use miswak.